Reduced bacillary load in elderly patients with active extrapulmonary and pulmonary tuberculosis in Peru: analysis of confirmatory culture after acid-fast bacilli test - Moya-Salazar, Jeel; Samán, Jonathan; Pasco, Israel A.; Moya-Salazar, Marcia M.; Rojas-Zumaran, Víctor; Contreras-Pulache, Hans (Frontiers in Microbiology, 2024)
Background: Older adults with tuberculosis (TB) present unusual clinical features and can be challenging to diagnose. Culture after evaluation of sputum smear (AFB) may result in improved diagnosis performance, however it has not yet been evaluated in Peruvian older adults. We aimed to evaluate the diagnostic relation of TB culture after the AFB in patients aged ≥65 years derived for the diagnosis of pulmonary (PTB) and extra-pulmonary (EPTB) in Lima, Peru.A cross-sectional study was developed in Lima, Peru, in order to evaluate the relationship of TB culture after AFB test in older adults (≥65 years) during the PTB and EPTB diagnosis. The frequency of contaminated cultures and the discrepancies between the conventional AFB test and Ogawa-Kudoh culture were analyzed.Results: Of the 10,461 sputum and 2,536 extrapulmonary samples analyzed during 2015-2017, PTB was diagnosed in 282 (2.7%) and EPTB in 88 (3.5%), respectively. The performance of AFB in the diagnosis of PTB had a sensitivity of 78.2% and specificity of 99.8%. The performance of AFB in EPTB had a sensitivity of 45.5% and specificity of 99.9%. Negative AFB with positive culture was more frequent in ≥82 years (p=0.031). We determined a good agreement in the diagnosis of PTB (κ=0.84) and moderate for EPTB (κ=0.55).Our findings suggest that diagnosis through culture should be performed after the AFB smear evaluation due to the moderate performance of AFB, especially in patients ≥82 years old.